2016
DOI: 10.1134/s002136401624005x
|View full text |Cite
|
Sign up to set email alerts
|

Graphite on graphite

Abstract: We propose potential geometry for fabrication of the graphite sheets with atomically smooth edges. For such sheets with Bernal stacking, the electron-electron interaction and topology should cause sufficiently high density of states resulting in the high temperature of either spin ordering or superconducting pairing.Comment: 4 pages, 1 figure, English version of paper published in Pis'ma ZhETF 104, 888--891 (2016

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
0
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(91 citation statements)
references
References 52 publications
4
85
0
2
Order By: Relevance
“…For a d-wave superconductor Volovik predicted an H 1/2 dependence associated with extended quasiparticle states near line nodes. 25 This effect was first observed by Moler et al 26 in a cuprate superconductor. It has been suggested that this H 1/2 dependence is modified to HlnH at low fields in a dirty superconductor.…”
Section: Discussionmentioning
confidence: 75%
“…For a d-wave superconductor Volovik predicted an H 1/2 dependence associated with extended quasiparticle states near line nodes. 25 This effect was first observed by Moler et al 26 in a cuprate superconductor. It has been suggested that this H 1/2 dependence is modified to HlnH at low fields in a dirty superconductor.…”
Section: Discussionmentioning
confidence: 75%
“…Here we show that the physical mechanism, responsible for above non-BCS behavior of overdoped LSCO, stems from the topological fermion condensation quantum phase transition (FCQPT) accompanied by so-called fermion condensation (FC) phenomenon generating flat bands [8][9][10][11][12][13][14] . We note that flat bands and extended saddle point singularity play important role in the theory of HTSC, see e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These observations representing the intrinsic LSCO properties provide unique opportunities for checking and expanding our understanding of the physical mechanisms responsible for high-T c superconductivity. We note, that that knowing the responsible mechanism can open avenue for chemical preparation of high-T c materials with T c as high as room temperature [8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…[36], and for x = 7 from [37] (dash-dot line), and introduce each one in Eq. (20) to perform the integrals numerically. The difference between the first two curves and the third one is small in the 20 K < T < 80 K interval and for T > 80 K it widens progressively.…”
Section: A Lattice Specific Heatmentioning
confidence: 99%
“…[16] and references therein), and its superconducting counterpart that evolves as γ 0 when the temperature approaches zero. Secondly, there is a quadratic αT 2 term for zero magnetic field [17][18][19] below T c (not exhibited in conventional superconductors), which changes to a H 1/2 T component in the presence of an external magnetic field [20] H, attributable to the superconducting part of the electronic specific heat C es . The reported values for this two constants depend strongly on the conditions of each experiment [17] and on the theoretical method used to relate the different parts of the total specific heat.…”
Section: Introductionmentioning
confidence: 99%